The Journey of Sinbad in the Poetry of Salah Abdel Sabour Spiritual Identification and Wrestling Destinies - بووشمة معاشو (Milev Journal of Research and Studies, 2023)
proceeds to use the expressive and suggestive field of the symbol of Sinbad. This study aims atassessing to what extent the poet succeeded in depicting his experience in life, and how he created similar relations between Sindbad voyage and his own voyage through life? Thus, loading this experience with a poetic intensity and sensorial focus, stored by myth and symbol, and accordingly, the study dealt with the topic in a structural approach that traces how the features of Sinbad penetrated into the text and revealed the mechanisms of the employment of mythology such as absorption and dissolution, which is expressed in identification that, stored by myth and symbol, and accordingly, the study dealt with the topic in a structural approach that traces how the features of Sinbad penetrated into the text and revealed the mechanisms of the employment of mythology such as absorption and dissolution, which is expressed in identification that reflects the experience and its conformity with the process of life.